Penyuluhan Budidaya Hortikultura sebagai Implementasi Program Kolaborasi Sosial Membangun Masyarakat di Lahan Kritis Desa Wonopringgo - Handriatni, Ari; Ariadi, Heri; Sajuri, Sajuri; Sudarmaji, Arief; Saparso, Saparso; Priswanto, Priswanto; Samego, Bony; Taufiq, Ibnu Jafar; Anggita, Riris; Tamam, Ibnu; Septiana, Diana K (Jurnal Penelitian dan Pengabdian Masyarakat, 2024)
Horticultural vegetables are one of the commodities that are widely cultivated in the tropics. The information is tried to be applied in the implementation of the Collaborative Social Building Community (KOSABANGSA) 2023 program. The purpose of this kosabangsa program is to determine the level of understanding of farmers on the cultivation system of horticultural vegetables. The method of service in the 2023 Kosabangsa program activities was carried out observatively and kuesioenr sharing conducting direct counseling in Wonopringgo Village, Pekalongan. The results of identifying the impact of this service showed that there was a very significant increase in farmers' understanding (50% increase by farmers) regarding horticultural vegetable cultivation. In addition, there was also an increase in knowledge by farmers about the types of horticultural vegetable commodities. From the original only 22 farmers who understood about horticultural vegetable commodities, after the extension there were 27 farmers who understood. The most noticeable impact is the increase in farmers' understanding of the horticultural vegetable cultivation system on critical agricultural land. This is evidenced from the beginning (before counseling) only 5 farmers who understand, but after counseling increased drastically to 26 farmers. Farmers also feel that this extension activity provides great benefits for them, so this program is very worthy of being developed further. The conclusion from the results of this service is that the majority of farmers in Wonopringgo village really understand the concept of horticultural vegetable cultivation which can be implemented on marginal land with various types of suitable vegetable commodities.